Expressão gênica de FOXP3, indoleamina 2,3 dioxigenase, IL10 e CSF1 em útero de vacas que receberam infusão intrauterina de antígenos maternos e paternos no período peri-ovulatório - Junqueira, Talita Vieta (2015)
In cattles, most of pregnancy losses occurs at the beginning of gestation, notably from the 7th to the 16th day of the cycle, a period in which, the embryo depends entirely on the uterine environment to survive and to start their preimplantation growth. During this period, the embryonic death after embryo transfers performed in vitro (TE-IVP) or in vivo (TE-OM) is on average nearly twice as high as that produced by natural mating or artificial insemination (AI). The recipient sensitization against the paternal and maternal MHC molecules of allogeneic embryo might be one of the causes of high rates of pregnancy loss observed after TE. Studies in humans and in various species have pointed that the sensitization with conceptus antigens may affect the reproductive performance facilitating the recognition and the maternal acceptance of allogeneic embryo through induction of cytokyne and immunoregulatory cells in the the uterine microenvironment. The purpose of this study is to determine whether simultaneous or separate administration of paternal and maternal antigens in the uterus of the cows embryo recipientes, during the estrus, increases the expression of genes which can facilitate recognition and development of allogeneic embryos during early pregnancy. Forty-five crossbed cows were evaluated. The animals were divided in four treatments: T0: control; T1: Semen; T2: PBMCs and T3: PBMCs+Semen. The cows were estrus synchronized and received antigens in the uterine body on the estrus day. Uterine biopsies were collected in vivo on D0 for control, and after seven (D7) and fourteen (D14) days after the estrus and administration of antigens in order to evaluate the treatment effect on the uterine environment of the receiving at the moment of the anovoluation procedure would occur in TE-IVP, and during the period in which the bovine embryo would have their preimplantation growth, respectively. The gene expression was evaluated in real time PCR, and then transcribed from FOXP3, IDO, IL-10 and CSF-1 were detected in all RNA samples extracted from uterine biopsies. Semiquantitative analyses of relative gene expression among the control and the treat groups demonstrated that none of the treatments significantly incresed those gene expressions. Furthermore, at D14 all the treatments leaded to a decline in amount CSF-1 transcripts and, further, treatment with both antigens also to a drop in the abundance of IL-10 transcripts. In conclusion, the isolated or simultaneous antigens admnistration in the in the uterus of IVP embryo recipient cows seems not to increase the maternal tolerance to alloantigens embryo nor benefit conditions for their growth and preimplantation development, at least with regard to the effect mediated by FOXP3, IDO, IL- 10 and CSF-1 on D7 and D14 in the estrous cycle.